2018
DOI: 10.1007/978-3-319-89327-3_7
|View full text |Cite
|
Sign up to set email alerts
|

Locomotion and Telepresence in Virtual and Real Worlds

Abstract: We present a system in which a human master commands in a natural way the locomotion of a humanoid slave agent in a virtual or real world. The system combines a sensorized passive locomotion platform (Cyberith Virtualizer) for the walking human, the V-REP simulation environment, an Aldebaran Nao humanoid robot with on-board vision, and a HMD (Oculus Rift) for visual feedback of the virtual or real scene. Through this bidirectional human-robot communication, the human achieves a telepresence that may be useful … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Simplified Model Control Layer Using the simplified models as in (5), it can be easily shown that the CoM asymptotically converges to a constant DCM, while the DCM, (see Eq. ( 6)) has an unstable first-order dynamics.…”
Section: Walking Controller Architecturementioning
confidence: 99%
See 2 more Smart Citations
“…Simplified Model Control Layer Using the simplified models as in (5), it can be easily shown that the CoM asymptotically converges to a constant DCM, while the DCM, (see Eq. ( 6)) has an unstable first-order dynamics.…”
Section: Walking Controller Architecturementioning
confidence: 99%
“…The architecture for human motions retargeting and humanoids teleoperation that we detail in this paper in an illustrative manner, is inspired by the work of A. Spada et al [5]. We address the basic theoretical aspects as well as treating implementation related issues utilizing the iCub humanoid robot platform [6] [7], which uses YARP [8] as middleware for communications, as our test bench to perform given manipulation tasks and walking.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, most of the current mobility based teleoperation interfaces (e.g. [15], 2377-3766 © 2019 IEEE. Personal use is permitted, but republication/redistribution requires IEEE permission.…”
Section: Introductionmentioning
confidence: 99%